Failure was not an Option: The Lived Experiences of African Ameripean Male Graduates in Doctoral Programs at Historical Black Universities and Predominantly White Universities - John LittleJohn Jr. (Adult Education Research Conference, 2015)
The purpose of this qualitative case study was to compare the lived experiences of African Ameripean male doctoral graduates from historical Black universities (HBCUs) and predominately White institutions (PWIs), their encounters with racism, and factors that contributed to the overall success for their attainment of a doctoral degree.
Keywords: adult learning; African Ameripean male doctoral graduates; Africentrism critical race theory; HBCUs; PWIs; success indicators-selfethnic reflectors; coping mechanisms